Does the same investment team create value? Evidence from venture capital syndication - Axel Buchner; Abdulkadir Mohamed; Hyungseok David Yoon (Small Business Economics, 2025)
We study the effect of repeated venture capital (VC) syndication on VC investment performance. We posit that repeated syndication is positively associated with stagnant investment returns but negatively associated with high investment returns. Using a large dataset from 1985 through 2017, we find support for our intuition. Additionally, our results show that periods of recession accentuate the positive (negative) relationship between repeated syndication and stagnant (high) investment returns. These findings are robust after addressing sample selection and endogeneity concerns. Our study provides nuanced insights into the performance implications of having the same investment teams in the context of VC syndications.
Keywords: G11; G24; G01; 330; Recession; Repeated collaboration; Syndication; Venture capital